Transgenic mice expressing rabbit C-reactive protein are resistant to endotoxemia - Xia, Dongyuan (The National Academy of Sciences of the USA, 1997)
C-reactive protein (CRP), the prototypic acute-phase reactant in humans, is synthesized in liver in response to a wide variety of inflammatory stimuli. We have generated a line of transgenic mice that express rabbit CRP from the rat phosphoenolpyruvate carboxykinase (PEPCK) promoter in response to gluconeogenic signals. Here we show that transgenic mice expressing high levels of CRP were partially protected from a lethal challenge of bacterial lipopolysaccharide compared with littermates in which CRP expression had been suppressed. Similar protection was observed with challenges from platelet-activating factor (PAF) and the combination of tumor necrosis factor α (TNF-α) plus interleukin 1β, but not with TNF-α alone. We further demonstrate that although PAF was able to bind CRP, the mechanism by which CRP provides protection probably does not involve sequestration of PAF. The biologically inactive precursor of PAF, lyso-PAF, also bound CRP but did not render the transgenic mice sensitive to PAF when CRP-expressing animals were simultaneously challenged with PAF and an excess of lyso-PAF. These results suggest that CRP functions in vivo by modulating host defense systems.